2009
DOI: 10.1159/000235736
|View full text |Cite
|
Sign up to set email alerts
|

Psychosomatic Assessment

Abstract: The primary goal of psychosomatic medicine is the incorporation of its operational strategies into clinical practice. The traditional attitude toward disease and the functional/organic dichotomy were criticized by George Engel in the early sixties. Only recently, however, there has been increasing awareness of the limitations of disease as the primary focus of medical care. It is not that certain disorders lack an organic explanation; it is our assessment that is inadequate in most clinical encounters. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
0
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 173 publications
(134 reference statements)
1
72
0
5
Order By: Relevance
“…In order to diagnose and treat medically ill patients with psychological distress properly it is essential to understand many factors that go beyond DSM-IV, such as the patients' life history, temperament and health-related behaviors [31] . This inadequacy in diagnostic assessment has been suggested to be the cause of the often inconsistent results in psychosomatic studies [32] and may have contributed to the inconsistent findings of the studies included in this review. The inconsistent findings across studies and the inability to draw firm conclusions might lead to the suggestion that there is little reason to continue to investigate the relative association of post-ACS depression subgroups with cardiac prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…In order to diagnose and treat medically ill patients with psychological distress properly it is essential to understand many factors that go beyond DSM-IV, such as the patients' life history, temperament and health-related behaviors [31] . This inadequacy in diagnostic assessment has been suggested to be the cause of the often inconsistent results in psychosomatic studies [32] and may have contributed to the inconsistent findings of the studies included in this review. The inconsistent findings across studies and the inability to draw firm conclusions might lead to the suggestion that there is little reason to continue to investigate the relative association of post-ACS depression subgroups with cardiac prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, si los análisis sobre los costes-beneficios de las intervenciones sanitarias tuvieran en cuenta dicha información "light", las conclusiones respecto a cuáles son los servicios que producen más salud, a menor coste, podrían ser diversas (Kaplan, 2003). Asímismo, dicha información es fundamental para un adecuado juicio clínico que tenga en cuenta la respuesta individual al proceso de enfermedad (Fava & Sonino, 2009;Tomba & Bech, 2012). En la actualidad, dicha información puede ser evaluada mediante escalas e índices válidos y fiables, desarrollados por la clinimetría en el contexto de la investigación y práctica psicosomática (Fava & Sonino, 2009;Tomba & Bech, 2012).…”
Section: Conclusionesunclassified
“…No es que ciertos trastornos no tengan explicación; es que, en muchos casos, nuestra evaluación es inadecuada, dado que no refleja una perspectiva psicosomática global (Fava & Sonino, 2009;Sonino & Peruzzi, 2009). …”
Section: Conclusionesunclassified
“…Lattanzio et al conducted a large cluster randomized clinical trial of 1914 patients and found that an intensive 3-day educational intervention was able to improve the ability of geriatricians to diagnose depression in older persons (sensitivity improved from 35 to 49% and specificity from 88 to 91%) [18]. From this evidence, it appears that screening is not sufficient on its own but that it can assist shared decision-making and together with a good intervention may produce worthwhile benefits [19]. There is much interest in a package of collaborative care that can be combined with a screening program with good results, at least in the short term [20].…”
Section: Why Do Physicians Have Difficulty Diagnosing Depression In Tmentioning
confidence: 99%